Developing strengths-based project teams - Buelt, Martha; Plowman, Connie (Portfolio and project management collection, 2018)
1. Introduction: the how and the why -- 2. Definitions: staying aligned -- 3. History: an overview of strengths philosophy and strengths-based project teams -- 4. Starting point: developing your strengths as a project manager -- 5. Mapping: connecting strengths and project management -- 6. Process: cultivating a strengths-based project team -- 7. Sustaining: keeping a strengths-based project team culture going -- 8. Action plan: make an investment -- Appendix A. Resources -- Appendix B. Templates and examples -- Appendix C. Connecting strengths and project management -- Appendix D. Strengths conversational prompts for project teams -- Index